Determinantes sociais do absenteísmo de diabéticos às consultas especializadas - Leal, Marcelle Lemos (2021)
Introduction: Diabetes Mellitus (DM) as a chronic disease requires regular monitoring by health services and absenteeism from medical appointments, which is frequent in our health scenario, makes it difficult to control the disease and access other patients to the health service. Objective: To analyze absenteeism in specialized appointments with diabetics scheduled by the Sistema de Centrais de Regulação (SISREG) in the Sistema Único de Saúde in Espírito Santo (ES). Methods: Cross-sectional study carried out using primary and secondary data with 472 diabetics ≥ 18 years of age scheduled appointments with an endocrinologist at SISREG-ES. A questionnaire was designed to assess access according to the dimensions of availability, financial viability and acceptability. To determine the reliability of the questionnaire, analyzes of reproducibility by test-retest and evaluation of internal consistency by Cronbach's alpha were performed. The configural structure and theoretical-empirical congruence were determined according to principal component analysis with varimax orthogonal rotation. The variables of the dimensions of access (availability, financial viability and acceptability) were used to estimate the association with absenteeism by means of logistic regression for crude and adjusted analyzes. A hierarchical model of the social determinants of health (SDH) of diabetic absenteeism was developed at five levels: socioeconomic and demographic, access to health, psychosocial, behavioral and clinical services of diabetes mellitus. Associations in the model were analyzed using multilevel logistic regression. Results: Three scientific articles were produced that addressed the absenteeism of diabetics to appointments with the endocrinologist at SUS in ES. Article 1 (accepted) originated a questionnaire on diabetic access to consultation with an endocrinologist with 15 questions and three dimensions: availability (α of Cronbach 0.669), financial viability (α of Cronbach 0.526) and acceptability (α of Cronbach 0.568). In the second article, an association was identified between absenteeism and the variables: living less than 10 kilometers from the consultation provider (OR: 1.814; 95% CI: 1.166 - 2.823, p 0.008); need transportation (OR: 4,893, 95% CI: 2,540 - 9,424, p <0,001) and have financial expenses to attend the consultation (OR: 2,057, 95% CI: 1,230 - 3,441, p 0,006). In Article 3 the SDH associated with diabetic absenteeism were: per capita household income greater than R $ 499.00 (OR = 1.668, 95% CI: 1.009-2.756), waiting time (OR = 0.997, 95% CI: 0.995-0.999), consumption alcoholic beverages (OR = 1.821, 95% CI: 1.031-3.239), obesity (OR = 1.773, 95% CI: 1.134-2.773), use of oral hypoglycemic agents and insulin (OR = 2.2, 95% CI: 1.09- 4.44) and have DM complications (OR = 2.03, 95% CI: 1.297-3.179). Conclusion: The knowledge of the DSS related to the absenteeism of diabetics in SUS allowed to understand the processes that produce and are mediators of health inequalities, which is essential for it to be possible to seek ways of coping. The evidence produced can contribute to the evaluation of priorities and the implementation of the Care Network for people with DM, as well as to subsidize the reformulation of lines of care for this population in ES to minimize the high rates of absenteeism in Specialized Outpatient Care.